Nutritional evaluation of four optimized cassavabased complementary foods - Onabanjo, O.O.; Oguntona, C.R.; Maziya-Dixon, B.B.; Olayiwola, I.O.; Oguntona, E.B.; Dixon, A. (2008)
Complementary foods were formulated and their nutritional composition analyzed from three yellow and one white cassava varieties. The composites were analyzed for proximate, mineral, fatty acids and amino acids. The mean values for the proximate composition of the diets are moisture(41.4gkg-1)wet weight, ash (47.4gkg-1), crude protein(145.8gkg-1),crude fat(106.7gkg-1),crude fiber(21.1gkg-1),total carbohydrate(633. 5gkg-1),and energy(409.2kcal).The diets supplied adequate amounts of most minerals, except iron(about 65% of the standard).The composites contained all the essential amino acids with adequate chemicals core for most amino acids. The complementary dies contained moderate to high proportion of –linolenic acids (18:3n3)and a high proportion of linoleic acid(18:2n6),which resulted in a high total n-6total n-3ratio and a high linoleic -linolenic acids ratio. Micronutrient improved cassava varieties can be effectively used to formulate complementary food as acceptable micronutrients supplement.